Determination of Uranium, Plutonium, Neodymium, Gadolinium and Their Isotopes in UO2-Gd2O3 Spent Nuclear Fuels - Kim, Jung-Suk; Jeon, Young-Shin; Park, Soon-Dal; Park, Yong-Joon; Ha, Yeong-Keong; Song, Kyuseok (Asian Journal of Chemistry, 2012)
Determination of U, Pu, Nd, Gd and their isotopes in UO2-Gd2O3 spent nuclear fuels by isotope dilution mass spectrometry has been studied. The spent fuel samples were dissolved in 8 M HNO3 at 90 ºC for 16 h under reflux. This method involves two sequential anion exchange resin (AG 1X8 and 1X4) separation procedures and a Gd purification procedure with a cation exchange resin (AG 50WX8) separation. Each fraction isolated was analyzed by thermal ionization mass spectrometry. The contents of U, Pu, Nd, Gd and their isotopes (234U, 235U, 236U, 238U, 238Pu, 239Pu, 240Pu, 241Pu, 242Pu, 143Nd, 144Nd, 145Nd, 146Nd, 148Nd, 150Nd, 152Gd, 154Gd, 155Gd, 156Gd, 157Gd, 158Gd and 160Gd) in the spent fuel samples were determined by isotope dilution mass spectometric method (IDMS) using quadruple spikes (233U, 242Pu, 150Nd and 158Gd). The results obtained from IDMS were applied to burnup determination as a destructive method using 148Nd isotope monitor.